1995
DOI: 10.1049/sej.1995.0010
|View full text |Cite
|
Sign up to set email alerts
|

Industrial perspective on static analysis

Abstract: Static analysis within industrial applications provides a means of gaining higher assurance for critical software. This survey notes several problems, such as the lack of adequate standards, difficulty in assessing benefits, validation of the model used and acceptance by regulatory bodies. It concludes by outlining potential solutions and future directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 3 publications
0
22
0
4
Order By: Relevance
“…Static analysis is widely used within industry for the analysis of safety critical code (see [WCC95]). Whilst there are a number of commercial tools which include static analysis such as QAC [QAC99], CANTATA [IPL99], and LDRA Testbed [Ldr99], the static analysis component of the tools are mostly examining only static properties.…”
Section: Industrial Static Analysismentioning
confidence: 99%
“…Static analysis is widely used within industry for the analysis of safety critical code (see [WCC95]). Whilst there are a number of commercial tools which include static analysis such as QAC [QAC99], CANTATA [IPL99], and LDRA Testbed [Ldr99], the static analysis component of the tools are mostly examining only static properties.…”
Section: Industrial Static Analysismentioning
confidence: 99%
“…Static code analysis is the analysis of computer software that is performed without actually executing programs built from that software. This is in contrast to the analysis performed on executing programs which is known as dynamic analysis [2]. Empirical evidence from [3] and [4] showed that software maintenance consumed between 50% and 80% of the resources in the total software budget.…”
Section: Introductionmentioning
confidence: 98%
“…The static analysis method [2] is often used in the security analysis for computer software. Great efforts have been devoted to the development of static analyzers.…”
Section: Introductionmentioning
confidence: 99%